2022
DOI: 10.3390/nu14030692
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of Pediococcus acidilactici pA1c on HFD-Induced Mice

Abstract: Prediabetes (PreD), which is associated with impaired glucose tolerance and fasting blood glucose, is a potential risk factor for type 2 diabetes mellitus (T2D). Growing evidence suggests the role of the gastrointestinal microbiota in both PreD and T2D, which opens the possibility for a novel nutritional approach, based on probiotics, for improving glucose regulation and delaying disease progression of PreD to T2D. In this light, the present study aimed to assess the antidiabetic properties of Pediococcus acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 125 publications
(198 reference statements)
1
21
0
Order By: Relevance
“…Hence, we can hypothesize that pA1c activity needs not only the daf-16 effect, but all the insulin signaling pathway (IIS). These findings are consistent and support the data obtained from the study of pA1c supplementation in mice [ 22 ], in which it was seen that 12-week pA1c supplementation significantly attenuated body weight gain, mitigated glucose dysregulation by reducing fasting blood glucose levels, glucose tolerance test, leptin levels, and insulin resistance.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, we can hypothesize that pA1c activity needs not only the daf-16 effect, but all the insulin signaling pathway (IIS). These findings are consistent and support the data obtained from the study of pA1c supplementation in mice [ 22 ], in which it was seen that 12-week pA1c supplementation significantly attenuated body weight gain, mitigated glucose dysregulation by reducing fasting blood glucose levels, glucose tolerance test, leptin levels, and insulin resistance.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies in mice fed high fat and high sugar diets have demonstrated that Pediococcus acidilactici CECT9879 (pA1c) has beneficial properties on glucose homeostasis including an anti-hyperglycemic effects [ 22 ]. In this study, we have evaluated the metabolic activities of the probiotic strain Pediococcus acidilactici CECT9879 (pA1c) on C. elegans lipid accumulation, insulin/IGF-1 signaling (IIS), health span, oxidative stress, and aging, and its response to a high-glucose exposure.…”
Section: Introductionmentioning
confidence: 99%
“…plantarum IMC 510 can improve the blood parameters and suggest that its benefits are possibly limited in subjects showing haematologic alterations. Notably, a large number of studies showed that certain probiotics may be able to lower glycaemia and serum lipids, particularly in diabetic or hypercholesterolemic subjects in clinical (Jones et al, 2012; Khalili et al, 2022; Kocsis et al, 2020; Wang et al, 2018; Wu et al, 2017; Zhang et al, 2022) and in pre‐clinical research (Cabello‐Olmo et al, 2022; Marques et al, 2020; Ooi & Liong, 2010; Reamtong et al, 2021; Wang et al, 2012). Notably, last year, three probiotics were tested in a healthy rabbit (see details in Kadja et al, 2021) and improved the biochemical and haematological profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium longum and Lactobacillus reuteri could increase mucus layer thickness [ 56 , 57 ]. Pediococcus acidilactici pA1c increases the number of cupped cells, which promote the secretion of mucus glycoproteins and maintain an appropriate length of intestinal villi [ 58 ]. Oxidative stress may play a role in damaging glucose metabolism by impairing pancreatic β cells and insulin signalling pathways.…”
Section: Discussionmentioning
confidence: 99%